Waste and Structural Bias in Corporate Law: (A Study of American Law with Reference to Iraqi Law) - Ghalib Al Azzawi, Lect. Shymaa (Basra studies journal, 2025)
This research discusses two behaviors of a gray nature that are practiced by corporate managements, namely waste and structural bias, both of which exist in any legal environment, and does not mean that they are specific to the American legal environment. The American legal system, whether through common law courts or chancery courts, has not been able to combat them for reasons: First, the rule of evaluating the commercial decision that protects managers, as the purely commercial decision is evaluated by managers not by the judges. It is not the right of the judges to interfere in how the boards manage their companies, secondly, the same behaviors of waste and structural bias do not reach the level of breaching the duty of fiduciary loyalty, which is the essential duty on the directors, and are classified under the category of breaching the duty of fiduciary care, which is restricted by the rule of evaluating the commercial decision. So the directors are not held accountable for their negligence if they believe that their decision is based on a reasonable commercial purpose and that they made this decision in good faith without seeking Some of them to achieve private interests.